Optimization of motorized backpack mistblower for efficient application of insecticides against the bagworm, Metisa plana walker - Syed Mohamed, Syed Mazuan; Ishak, Insyirah; Omar, Dzolkhifli; Asib, Norhayu (Pakistan Agricultural Research Council, 2021)
Oil Palm (Elaeis guineensis Jacq.) is a crucial economic crop in Malaysia which has become susceptible towards pests and diseases. Studies showed the major leaf defoliator of oil palm in Malaysia is the bagworm, Metisa plana. Various spraying methods had been developed for controlling the bagworms. A ground study was conducted in FELDA Gunung Besout 04, Perak, with its main focus on mistblower application towards bagworms. Stihl SR420 mistblower was characterised by having 1.2L / min flow rate, produced volume median diameter of 80μm, and achieved spraying productivity of 2.58 hectares’ land size (approximately 350 oil palms) per man day. The study was to evaluate the efficacy of chlorantraniliprole (Altacor® 34.9WG), Bacillus thuringiensis kurstaki (DiPel® ES), cypermethrin (Hextar Cyper 5.5EC), flubendiamide (Takumi® 20WG) and B. thuringiensis MPOB Bt-1 (Ecobac-1 EC). The insecticides application rate was based on the manufacturer’s recommendation. The bagworms were monitored before treatment and at 3, 7, 15, 30, 45, and 70 days after treatment (DAT). Post-census showed that all insecticides were able to reduce the bagworm population below the economic threshold level (10 larvae/ frond) within 15 DAT. Both cypermethrin and MPOB Bt1 resulted in the highest mortality of bagworms which was 83%. Then, flubendiamide, chlorantraniliprole and Btk resulted in mortality rate of 82%, 75%, and 70% respectively. All aforementioned, insecticides applied were able to suppress the population up to 30 DAT.